Pilot randomised controlled trial of occupational therapy to optimise independence in Parkinson's disease: the PD OT trial. Issue 9 (13th March 2008) - Clarke, C E; Furmston, A; Morgan, E; Patel, S; Sackley, C; Walker, M; Bryan, S; Wheatley, K
Abstract : Objective: To perform a pilot trial of occupational therapy (OT) to optimise functional independence in Parkinson disease (PD) to assess accrual/withdrawal rates, acceptability, outcome measures, and inform sample-size calculation. Method: Non-demented patients with idiopathic PD and difficulties with activities of daily living (ADL) were recruited provided they had not received OT in the last 2 years and/or physiotherapy in the last year. Patients were randomised to immediate OT or OT after completion of the trial. Patients randomised to OT were assessed at home by an experienced therapist and then received six home treatment sessions over 2 months. Interventions were targeted at functional independence and mobility goals. Outcome measures were: Nottingham Extended Activity of Daily Living Scale, Rivermead Mobility Index, Unified Parkinson's Disease Rating Scale ADL scale, Parkinson's Disease Questionnaire 39, EuroQol-EQ-5D, Hospital Anxiety and Depression Scale, and health economics analysis. Results: 39 patients (25 male; mean age 73 years) were recruited from four centres over 16 months. The mean difference in NEADL at 8 months was 3.5 (95% CI −3.2 to 10.2). The mean difference in PDQ-39 Summary Score was 3.8 (95% CI −4.94 to 12.6). There were strong correlations between the PDQ-39 and other outcomes. The intervention was acceptable to patients, with a low withdrawal rate and good questionnaire completion. Conclusion: Randomisation to a trial of OT in PD is feasible. NEADL and PDQ-39 are relevant outcomes and provided data to inform sample size for an adequately powered randomised trial for which there is pressing need.